Exploring sitting posture and discomfort using nonlinear analysis methods. - Hermann, S. (IEEE Transactions on information technology in biomedicine)
The possibilities for describing sitting postural control using nonlinear methods was investigated during long-term driving. A total of 85 min of motorway driving intervals (n=12) were used for analysis. The results show that contrary to conventional analysis techniques, nonlinear measures were able to identify a threshold behavior describing the change in discomfort. Visual recurrence plots showed a clear change in the underlying dynamics after 1 hr of driving. The result was confirmed by the statistically significant differences in the stability and complexity of the COP time series, as explored using recurrence quantification analysis and spatio-temporal entropy. The findings of the experiment are consistent with the literature, and present a novel way to uncover transitions of discomfort stages in sitting behavioral research.